The impacts of brand experiences on customer satisfaction and electronic word of mouth - Bader Almohaimmeed (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The problem addressed in this study is that the impact of the customer experience on the achievement of positive customer outcomes is still unknown in Arabic restaurants. Hence, the aim of this study is to explore the effect of brand experience, as measured through sensory, emotional, behavioural, and intellectual brand experience, on customer satisfaction and customer electronic word of mouth (eWOM) as well as the effect of customer satisfaction on eWOM. Data were collected using an electronic questionnaire consisting of 18 items distributed to a convenience sample of Facebook users. A total of 311 valid responses were collected. The participants were asked to evaluate their satisfaction and eWOM based on 6 items and their brand experience based on 12 items. Using IBM SPSS AMOS, the study revealed that three dimensions of brand experience (sensory, emotional, and behavioural) were significantly related to customer satisfaction and eWOM. Intellectual brand experience, according to the results of the current study, had no significant effect on customer satisfaction or eWOM. This conclusion is highlighted at the end of the paper along with its implications and recommendations. The contribution of this study stems from the fact that it alerts organizations to the factors influencing customer behaviour that ultimately lead to positive outcomes.
Keywords: M00; M30; M31; M37; M39; C83; 650; sensory brand experience; emotional brand experience; behavioural brand experience; intellectual brand experience; brand experience; customer satisfaction; eWOM